Effect of Self-care Training based on Acceptance and Commitment Therapy on Perceived Stigma and Burden of Care in Caregivers of Patients with Schizophrenia: A Randomized Controlled Trial - Neda Rahmatnejad; Yadollah Jannati; Reza Ali Mohammad Pour; Hamideh Azimi Lolaty (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Stigma and burden of care in caregivers of patients with schizophrenia have negative effects on the patient and their families. This research aimed to determine the effect of self-care training based on Acceptance and Commitment Therapy (ACT) on perceived stigma and caregiver burden of schizophrenic patients. Materials and methods: This randomized clinical trial included 80 caregivers of schizophrenia patients in Sari Zare Hospital. Participants in intervention group received self-care training based on ACT in 8 sessions twice a week, while the control group received only routine care. The scores for stigma and care burden were measured in both groups before and after the intervention using Shamsaei stigma questionnaire and Zarit Burden Interview (ZBI, 22-item). T-test and paired t-test and descriptive statistical methods were used to analyze the data. Results: The mean changes of the total score for perceived stigma before and after the intervention were found to be significantly different between the intervention group (65.45±6.79) and the control group (80.25±10.34)(P<0.05). Also, intergroup comparison showed a significant difference in mean changes of the total scores for burden of care before and after the intervention between the intervention group (44.35 ± 6.37) and the control group (55.05 ±10.29) (P <0.05). Conclusion: According to current study, self-care training based on Acceptance and Commitment Therapy will improve perceived stigma and reduce burden of care in caregivers of patients with schizophrenia and such non-invasive interventions are recommended.